Analisis Faktor-Faktor yang Mempengaruhi Jumlah Kasus Tuberculosis di Kabupaten Lombok Timur menggunakan Model Spatial Autoregressive Poisson - Adini, Ertina Septia; Azizah, Efida; Hastuti, Siti Hariati; Ghazali, Muhammad (Jambura Journal of Probability and Statistics, 2025)
Tuberculosis (TB) is a deadly infectious disease caused by the bacteria Mycobacterium tuberculosis. According to the NTB Provincial Health Office, the number of TB cases in NTB Province was reported as many as 7,305 cases in 2019. East Lombok Regency in that year recorded 1,521 TB cases. The high number of TB cases in East Lombok Regency is an interesting reason to use statistical analysis techniques in modeling variables that influence the number of TB cases in East Lombok Regency. This study uses Spatial Autoregressive Poisson (SAR Poisson) analysis. This method is a development of the classical regression method by considering spatial dependence on the dependent variable, namely count data that follows the Poisson distribution. According to the results of the study, there is significant spatial dependence on the data based on the results of the Moran's I test. The results of the SAR Poisson modeling show that only the Population Density variable (X_4) has a significant effect on the number of TB cases in East Lombok Regency with a parameter value of -1.24 x 10^{-21}. The corrected determination coefficient showed quite high results with a value of 71.8%, which means that the model can explain most of the variability in the data, which is an indication that the model has a good fit and high relevance to the data. The results of the mapping of the comparison of actual data and the estimated value of TB cases from the SAR Poisson model showed similar results.